Wednesday

April 23, 2014

April 23, 2014

Posted by **JT** on Monday, July 19, 2010 at 9:16pm.

Subtract b2 from both sides a2 – b2 = a * b – b2

Factor both sides: ( a + b )( a – b ) = b(a – b )

Divide both sides by ( a – b)

( a + b ) = b

Since a = b,

- Algebra -
**Reiny**, Monday, July 19, 2010 at 10:24pmerror:

since a-b = 0, you are dividing by zero !!!!

**Related Questions**

Algebra - explain the logical error Square both sides to get a2 = b2

math - Show that the formula for a line through two points (a1,b1) and (a2,b2) ...

algebra homework - f(x) and g(x) are monic quadratic polynomials that satisfy ...

ALgebra - Indicate and explain the logical error in the following set of ...

math - Kahlil said that using the equation (a + b)2 = a2 + 2ab + b2, he can find...

math 213 - Kahlil said that using the equation he can find a similar equation ...

Maths - If cosec A – sin A=a3 , sec A – cos A =b3 , prove that a2 b2 (a2 + b2)=1...

math - Kahlil said that using the equation € (a + b)2 = a2 + 2ab + b2, , he can ...

MAT221 - 2.Use the following algebraic expressions for parts 4-6 of the ...

chem - rate=k[A2][B2]^2. by how much would the rate change if: i) [A2] is ...